Respuesta :

Answer:

b.) 3p=6 is not equivalent

Step-by-step explanation:

If you solve and do the same thing on both sides you will get every other solution except b.

MardyH

Answer:

The correct answer is b) 3p = 6

Step-by-step explanation:

First, we need to find p:

3p - 2 = 6p + 4

-2 = 3p + 4

-6 = 3p

-2 = p

Now, we just need to plug p's value into each question:

a) 3p = 6p + 6

3(-2) = 6(-2) + 6

-6 = -12 + 6

-6 = -6

Since -6 = -6, a is not the correct answer.

b) 3p = 6

3(-2) = 6

-6 = 6

Since -6 ≠ 6, b is the correct answer.

c) -6 = 3p

-6 = 3(-2)

-6 = -6

Since -6 = -6, c is not the correct answer.

d) -3p - 2 = 4

-3(-2) - 2 = 4

6 - 2 = 4

4 = 4

Since 4 = 4, d is not the correct answer.

Therefore, b is the correct answer.

ACCESS MORE